Partitioning Signed Networks - Traag, Vincent; Doreian, Patrick; Mrvar, Andrej (Advances in Network Clustering and Blockmodeling, 2020)
This chapter is concerned with signed networks, where each link is associated with either a positive (+) or negative sign (‐). Blockmodeling, as a way of partitioning social networks, started with a clear substantive rationale expressed in terms of social roles. However, the availability of algorithms for partitioning (unsigned) networks, based on ideas of structural equivalence, led to a rather mechanical application to simply partition social networks with a subsequent ad hoc interpretation of what was identified. Consistent with this, the approach known as structural balance theory has a clear substantive foundation. The chapter briefly reviews the basics of balance theory as it connects directly to partitioning signed social networks. It then reviews some methods for partitioning networks in practice, and examines how they connect to balance theory. The chapter also briefly explores how structural balance evolves through time in an empirical example of international alliances and conflict.